Implementasi AI Dalam Proses Pembelajaran di Perguruan Tinggi : Studi Kasus Penggunaan AI Di Prodi Ilmu Fisika - Dian Eka Chandra Wardhana; Sarwit Sarwono; Didi Yulistio; Agung Subakti; Jamaludin Jamaludin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Community service activities are carried out using the Penthahelix method. The stages of implementing the Pentahelix method in service activities with Enhanced Spelling Application material in the Class B Physics Study Program are: (1) establishing good communication and collaboration with all Pentahelix parties, (2) creating a clear, measurable and beneficial activity program for all parties, in this case the program used as service material is the EYD application for student writing purposes, (3) Use creative and innovative methods to attract student interest, (4) monitor and evaluate student activities when carrying out the use of the application periodically to ensure its effectiveness, (5) documenting service activities and results well. The results of service activities show that AI has the potential to revolutionize education, and the Unib Physics Study Program is at the forefront of exploring this potential. The implementation of AI in the Unib Physics Study Program has produced several positive benefits, and this program can become a model for other programs at other universities. However, there are also several challenges that need to be overcome before AI can be widely adopted in education.